Neurodevelopmental Disorders and Adaptive Functions: A Study of Children With Autism Spectrum Disorders (ASD) and/or Attention Deficit and Hyperactivity Disorder (ADHD) - Scandurra, Valeria; Emberti Gialloreti, Leonardo; Barbanera, Francesca; Scordo, Marirosa Rosaria; Pierini, Angelo; Canitano, Roberto (Frontiers in Psychiatry, 2019)
Autism spectrum disorder (ASD) and attention deficit and hyperactivity disorder (ADHD) are the two most common neurodevelopmental disorders observed in childhood. The DSM-5 accepts a combined diagnosis of ADHD and ASD, while the DSM-IV did not. The aim of this study was to identify and evaluate the adaptive profile of children and adolescents with a diagnosis of comorbid ADHD and ASD, in comparison with adaptive functioning in subjects with a diagnosis of only ASD or ADHD. Ninety-one children (77 boys, 14 girls), aging from 3.1 to 13.4 years (mean age: 8.3 ± 7.2), who met the criteria for a diagnosis of ASD and/or ADHD were enrolled. A neuropsychological evaluation involving cognitive and adaptive assessment was conducted using the Autism Diagnostic Observation Schedule – Second Edition (ADOS-2), the Conners’ Parent Rating Scale – Revised: Long Version (CPRS-R, Conners, 2001), the Wechsler Intelligence Scale – Fourth Edition or the Griffiths Mental Developmental Scales – Extended Revised, the Vineland Adaptive Behaviour Scale – Second Edition (VABS-II), and the Kiddie-Schedule for Affective Disorders and Schizophrenia – Present and Lifetime Version. As to the adaptive skills in the three groups evaluated, a worse general profile was ascertained in the ASD and in ASD plus ADHD groups in comparison with the ADHD-only group. With VABS-II evaluation, we found significant differences among the three groups across all domains and combined scores: Communication (F = 18.960; p < 0.001), Socialization (F = 25.410; p < 0.001), Daily Living Skills (F = 19.760; p < 0.001), Motor (F = 9.615; p < 0.001), and Adaptive Behavior Composite (F = 29.370; p < 0.001). Implications of neurodevelopmental double diagnosis such as ASD plus ADHD are discussed.